Kontribusi Fiqh Legal Maxim dalam Fatwa-Fatwa Ekonomi Syariah Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) - Aidil Novia (TSAQAFAH, 2016)
The paper aims to describe the use of Fiqh Legal Maxims (FLM) in fatwas issued by Dewan Syariah Nasional Majelis Ulama Indonesia (DSN- MUI) and compare it with Fiqh Legal Maxims (FLM) in the book of Majallah al-Aḥkâm al-‘Adliyyah. This paper based on some researchs show that maqâṣid syarî’ah can be seen in Fiqh Legal Maxims (FLM) in fatwas. These researchs written by Ali Ahmad al-Nadwi, Muhammad Ridwan ‘Abdul Aziz, Muhammad Tahir Mansoori, and Abu Umar Farook. The primary data of this paper are 89 fatwas issued by Dewan Syariah Nasional Majelis Ulama Indonesia (DSN- MUI) and analysed by content analysis. The paper shows that Fiqh Legal Maxims (FLM) used in 97% of fatwas, consist of 1-7 Fiqh Legal Maxims (FLM) in every fatwa. The most frequently used is “al-aṣl fî al-mu’âmalâh al-ibâḥah illâ an yadulla dalîl ‘ala taḥrîmihâ” as basic Fiqh Legal Maxims (FLM) in financial transaction (78 times). Fiqh Legal Maxims (FLM) related to islamic banking are most frequently used (174 times). There are 72 Fiqh Legal Maxims (FLM) related to Islamic economics and finance in the book of Majallah al-Aḥkâm al-‘Adliyyah and it can be used in the next fatwas will be issued by Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI).